2021
DOI: 10.1016/j.celrep.2021.108711
|View full text |Cite
|
Sign up to set email alerts
|

Nα-terminal acetylation of proteins by NatA and NatB serves distinct physiological roles in Saccharomyces cerevisiae

Abstract: Highlights d Nt acetyltransferases NatA and NatB have distinct roles in cellular processes d NatA is implicated in the maintenance of chromosomal integrity d NatB plays a more important role in cellular proteostasis than NatA

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(60 citation statements)
references
References 85 publications
7
53
0
Order By: Relevance
“…We observed significantly lower protein levels in the naa10Δ mutant ( Fig S1A ), which may not be explained by the observed very weak stability differences. Friedrich et al (2021) reported altered expression/transcription levels in the absence of NatA, which could explain the differences in protein abundance. To investigate this we used qPCR to quantify tFT-mRNA and detected a ∼40% reduction of the mRNA levels of the reporter in the absence of NatA ( Fig S1B ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We observed significantly lower protein levels in the naa10Δ mutant ( Fig S1A ), which may not be explained by the observed very weak stability differences. Friedrich et al (2021) reported altered expression/transcription levels in the absence of NatA, which could explain the differences in protein abundance. To investigate this we used qPCR to quantify tFT-mRNA and detected a ∼40% reduction of the mRNA levels of the reporter in the absence of NatA ( Fig S1B ).…”
Section: Resultsmentioning
confidence: 99%
“…Beside the changed degradation rates of UFD-substrates we also observed changed protein abundance in NatA mutants, which were potentially linked to altered mRNA levels (Fig S1A and B). Changed protein synthesis and transcription rates were already reported for NatA mutants and underline the vast cellular changes that are happening in these deletion strains (Friedrich et al, 2021). In some instances, these phenotypes made it difficult to review stability changes in cycloheximide chase experiments when protein levels were very variable between different genetic backgrounds.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The actual shape of the growth law curve depends degradation rates (I φ,α ). By analyzing the dataset from [14], we found that I φ,α is independent of growth rate, while I χ,k appears to be negatively correlated with the growth rate. This means that cells tend to produce proteins with faster translation speeds in slow-growth conditions, which can be an economic strategy and under evolutionary selection.…”
mentioning
confidence: 92%